Cláusulas escalonadas de solución de controversias: una aproximación a sus principales problemáticas - Rodríguez Uriol, Dario Andrés (Pontificia Universidad Católica del Perú, 2023)
The multi-tiered dispute resolution clauses are a very popular type of arbitration agreement nowadays. These clauses provide that, in order to resolve disputes arising out of a contractual relationship, the parties may or should have recourse to more than one dispute resolution mechanism, which will be used progressively, one after the other. Although this type of covenants may present advantages for the parties, they may also become problematic clauses, which, when inadequately designed or managed, may be a source of additional conflicts to those already arising. For this reason, this article will analyze the main problems that arise in connection with this type of agreement. More specifically, three issues are analyzed in relation to the pre-arbitration stages: their enforceability, the most relevant factors to be taken into account for their execution and compliance, and the consequences of non-compliance for the arbitration process.

Las cláusulas escalonadas de solución de controversias son un tipo de convenio arbitral muy popular hoy en día. Estas cláusulas prevén que, para solucionar las controversias que surjan en torno a una relación contractual, las partes podrán o deberán recurrir a más de un mecanismo de solución de controversias, los cuales serán utilizados de forma progresiva, uno después de otro. Si bien este tipo de pactos pueden presentar ventajas para las partes, también pueden llegar a ser cláusulas problemáticas que, de diseñarse o gestionarse de forma inadecuada, pueden ser fuente de conflictos adicionales a los ya surgidos. Por ello, en el presente artículo, se analizarán las principales problemáticas que surgen en torno a este tipo de acuerdos. Más concretamente, se analizan tres problemáticas en torno a las etapas pre arbitrales: su obligatoriedad, los factores más relevantes a tener en cuenta para su ejecución y cumplimiento, y las consecuencias que su incumplimiento trae para el proceso arbitral.
Multi-tiered dispute resolution clauses: an approach to their main problems
Keywords: Arbitration; Arbitration agreement; Multi-tiered dispute resolution clauses; Self-compositive dispute resolution mechanisms; Effective judicial protection; Admissibility of arbitration; Jurisdictional incompetence; Arbitraje; Convenio arbitral; Cláusulas escalonadas; Solución de controversias; Mecanismos autocompositivos; Tutela jurisdiccional efectiva; Admisibilidad del arbitraje; Incompetencia jurisdiccional; https://purl.org/pe-repo/ocde/ford#5.05.00